ANALISIS GOOD CORPORATE GOVERNANCE, FREE CASH FLOW, LEVERAGE TERHADAP EARNING MANAGEMENT, DAN SHAREHOLDER WEALTH PADA PERUSAHAAN SEKTOR JASA YANG TERCATAT DI BURSA EFEK INDONESIA - ADITAMA, BUNTAR PERWIRA; RIYADI, SLAMET; INGGA, IBRAHIM (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRACTThe phenomenon of the "megadolar" case that occurred in Enron Corporation and the profits stated over stated at PT. Kimia Farma caused by earnings management. Earning management results in reporting on financial statements asymmetry with the actual situation. This can bring huge losses to shareholders because financial statements are the main basis for shareholders in conducting business transactions. Utami (2005) in his research stated that Indonesia is the country with the most rice earning management. Thus it is important for investors and shareholders in Indonesia to look at things that can trigger earnings management and what can prevent earnings management. In this study the researchers tested the effect of good corporate governance, free cash flow, and leverage on wealth earning management and shareholders. The researcher examines the effect of good corporate governance as a variable that can prevent earnings management and test free cash flow and leverage as triggers for earnings management.In this study using a sample of 178 service sector companies taken through the Yamane method with a sampling method namely purposive sampling in the 2014-2016 period. Data analysis and hypothesis testing in this study using the Partial Least Square Path Modeling (PLS-SEM) method. The results showed that good corporate governance proved to have a significant negative effect on earnings management while shareholders in wealth had a significant positive influence. Free cash flow proved to be insignificant to earning management while shareholder wealth had a significant positive effect. The leverage variable proved to have a significant negative relationship to earnings management as well as wealth shareholders. Keyword:  good  corporate  governance,  free  cash  flow,  leverage  earning management, shareholder wealth.